The Value of African Wisdom: Reflections on Modern Education in Uganda. - Sekiwu, Denis (Kabale University, 2024)
African Wisdom has remained on the verge of collapse arising from Western knowledge dominance. In the global knowledge revolution, however, all knowledge is critical in social transformation. This study examines the value of African wisdom in modern education. It interrogates the role of African wisdom in developing modern competence education. Thus, the article documents the philosophical scope of African wisdom as naturalized epistemology. It explores the status of African wisdom in the wake of colonialism, painting the hegemonic character of Western knowledge production. It empirically examines the value of African Wisdom in the development of competency-based education. Using qualitative research on Uganda, the paper analyzes the hidden educational treasure embedded in two African wisdom sources. Researchers used quantitative research to document the benefits and challenges of integration of African wisdom in modern education. Finally, the paper recommends transformative education in the social reconstruction of African education.